PENINGKATAN HASIL BELAJAR IPA MELALUI MODEL PBL PADA MASA PANDEMI UNTUK SISWA KELAS V: Array - Nur Fitria; Yulia Anggraini (eductum: Jurnal Literasi Pendidikan, 2022)
Implementation of online learning makes students become bored so that it has an impact on student learning outcomes. Through the application of the learning model in CAR research, it is hoped that it can improve student learning outcomes. The purpose of this PTK research was to (1) describe the effect of the problem-based learning model (PBL) during the pandemic on students' science learning outcomes, (2) improve science learning outcomes during the pandemic for fifth grade students of UPT SDN 26 Prambangan, Kebomas District, Regency. Gresik Academic Year 2020/2021. The research method used is descriptive qualitative method with the type of classroom action research (PTK). The design of this study used the Kemmis and Mc. Teggart. The research was conducted in the even semester of the 2020/2021 academic year, namely March- April. The PTK research subjects were grade 5 students of SDN 26 Prambangan, Kebomas District, Gresik Regency with a total of 11 students consisting of 5 male students and 6 female students. The object of research is the learning outcomes of students. Data collection techniques used in the study were observation, tests, and documentation. CAR is carried out in two cycles through planning, acting, observing and reflecting. Data were analyzed descriptively and presented in the form of a bar chart. The results showed a significant increase in science learning outcomes, namely in the pre- cycle amounted to 63.64%, the first cycle was 81.82% then in the second cycle it increased to 90.9%. This means an increase of 9.08%. Thus the use of the PBL model during a pandemic can improve the science learning outcomes of grade V students of UPT SDN 26 Prambangan, Kebomas District, Gresik Regency